Analisis Perlakuan Akuntansi Aset Tetap pada Lembaga Amil Zakat, Infaq dan Shadaqah Muhammadiyah (LAZISMU) Menteng Jakarta Pusat - Fatma Yeni (Universitas Muhammadiyah Prof Dr Hamka, 2020)
The purpose of this study is to analyze the application of fixed accounting at the Amil Zakat Institute, Infaq and Sadaqah Muhammadiyah (LAZISMU) Menteng, Central Jakarta, which starts from the verification process to the presentation process of the fixed assets. In analyzing data, quantitative descriptive methods are used, namely by conducting between the theories used in research with their application in LAZISMU operations. The results showed that in accounting for fixed assets are grouped into 2 namely vehicles and inventory. Obtained from the material value of the assets presented are several accounts that have an immaterial value. LAZISMU complies with generally accepted guidelines or standards namely PSAK No. 16. The interesting thing found in this research is that the fixed assets of vehicles consisting of ambulances are included in the group of assets under management rather than as fixed assets.